Migração de Sistemas Monolíticos para Microserviços: Uma Abordagem Híbrida sem Downtime - Arraes, Augusto Flávio Albuquerque; Sampaio, Américo; Medeiros, Otavio; Mendonca, Nabor das Chagas (Anais do Workshop em Clouds e Aplicações (WCGA); 2019: Anais do XVII Workshop em Clouds e Aplicações, 2019)
The recent Microservices paradigm is based on building a system as a set of small distributed services developed in an independent fashion that are deployed, scaled and replicated in a transparent way as it was a single application. Several organizations that are adopting this paradigm have to cope with the challenge to migrate current traditional monolithic applications in production to microservices, preferably, without having to schedule maintenances to take the application offline. This paper presents an approach for hybrid migrating to microservices with no downtime and practically no changes in the monolithic code. A real application is used as a proof of concept to demonstrate that the proposed approach enables to go forward or backward among different versions of the application without needing to take the application offline, considering code or data changes. Moreover, an evaluation performed in the cloud demonstrates that this work does not introduce significant performance or costs overhead and still enables to support higher loads in the monolith, due to the removal of part of its functionality to be processed in microservices.